Biomechanics research in ski jumping, 1991-2006 - Schwameder, H. (Sports Biomechanics, 2008)
In this paper, I review biomechanics research in ski jumping with a specific focus on publications presented between 1991 and 2006 on performance enhancement, limiting factors of the take-off, specific training and conditioning, aerodynamics, and safety. The first section presents a brief description of ski jumping phases (in-run, take-off, early flight, stable flight, and landing) regarding the biomechanical and functional fundamentals. The most important and frequently used biomechanical methods in ski jumping (kinematics, ground reaction force analyses, muscle activation patterns, aerodynamics) are summarized in the second section. The third section focuses on ski jumping articles and research findings published after the establishment of the V-technique in 1991, as the introduction of this technique has had a major influence on performance enhancement, ski jumping regulations, and the construction of hill profiles. The final section proposes topics for future research in the biomechanics of ski jumping, including: take-off and early flight and the relative roles of vertical velocity and forward somersaulting angular momentum; optimal jumping patterns utilizing the capabilities of individual athletes; development of kinematic and kinetic feedback systems for hill jumps; comparisons of simulated and hill jumps; effect of equipment modifications on performance and safety enhancement.